Evaluation of efficacy of regimens containing zidovudine, stavudine and tinofovir - Adiga, Sachidananda; Malawadi, BN; Adiga, Usha (International Journal of Medical Research and Review, 2016)
Objective: Aim of the study , was to compare the efficacy of regimens containing zidovudine, stavudine and tinofovir by comparing CD4 counts of patients at the end of 2 years .We also aim to evaluate their efficacy, by comparing basal CD4 count and CD4 count at 2 years in patients on these three regimens. Methodology: A retrospective observational study was conducted on 128 HIV patients, receiving various antiretroviral regimens in a teaching hospital in coastal Karnataka. Data of patients who were diagnosed to be HIV positive, receiving HAART and were attending the hospital for regular follow up once in six months was collected in data extraction form. Regimens containing zidovudine, stavudine and tinofovir were evaluated by comparing 2 year CD4s of patients. Effectiveness of each regimen was evaluated by comparing basal CD4 count with CD4 count at the end of 2 years. Results: We did not find any significant difference in basal CD4 counts in 3 regimens. CD4 count at the end of 2 years differed significantly (P<0.05) between the groups. Stavudine receiving patients had significantly higher (P<0.05) CD4 count as compared to AZT treated patients. Patients treated with TDF had highly significant (P<0.0001) elevation in CD4 count compared to that of AZT. However d4T and TDF didn’t have significant difference in CD4 counts at the end of 2 years. Patients in each group had extremely significant elevation in CD4 counts (p=0.0000) as compared to basal levels. Conclusion: We can conclude that TDF containing regimen is more effective than that containing AZT or d4T,based on the CD4 count at the end of 2 years and the extent of elevation of CD4 count.